Evaluating the Role of Artificial Intelligence in Optimizing International Logistics and Distribution Networks - Diar Rachmat (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2026)
The rapid globalization of trade and the increasing complexity of supply chains have led to the need for more efficient logistics systems. Artificial Intelligence (AI) has emerged as a transformative technology that can optimize international logistics and distribution networks. This study aims to evaluate the role of AI in improving the efficiency and effectiveness of logistics operations by examining its applications in demand forecasting, route optimization, inventory management, and decision-making processes. This study employs a qualitative literature review using a structured review approach to synthesize findings from relevant academic publications. A total of 31 sources, including journal articles and related scholarly publications, were analyzed based on their relevance to AI applications in international logistics and supply chain operations. The analysis identifies three major thematic areas: the integration of AI in global supply chains, the challenges and opportunities associated with AI adoption, and the impact of AI on decision-making and operational efficiency. The findings indicate that AI enhances logistics performance by improving forecasting accuracy, optimizing transportation routes, and supporting data-driven decision-making processes. However, the literature also highlights several barriers to implementation, particularly high initial investment costs, data security concerns, and organizational resistance to technological change. The study concludes that while AI offers substantial benefits, successful implementation requires not only technological capability but also organizational readiness and effective data governance. By synthesizing existing research, this study provides a structured perspective on the role of AI in logistics optimization and highlights key factors influencing its successful adoption in global supply chains.